Book Review - Gaddis, John Lewis; Harris, Robert; Paxman, Jeremy; Sauvant, Karl P. (Tufts Archival Research Center, 2005)
Volume 7, Issue 1. Winter. Strategies of Containment. A Higher Form of Killing: The Secret Story of Chemical and Biological Warfare. The Group of 77: Evolution, Structure, Organization. Book Review